Franks and Saracens: Reality and Fantasy in the Crusades By Avner Falk (London: Karnac Books, 238 pages.) (American Journal of Islam and Society, 2015)
Avner Falk’s Franks and Saracens: Reality and Fantasy in the Crusades ispresented in the opening pages as the first psychoanalytic study of the Crusades.The book is written for both a general readership and an academic audience.The fact that it was published by Karnac Books, one of the premierepublishers of psychoanalytic theory and practice, leads one to think that thepsychoanalytic community is a particularly important audience. The book’sopening chapter, “Us and Them,” introduces psychoanalysis as a theoreticalsource for helping us to think about cultural identity and conflict, particularly“us vs. them” identity conflicts. Following this general foregrounding of theCrusades and psychoanalytic theory, the author turns to how the Crusaders,namely, the “Franks,” created a larger fantasy that drove their violent engagementwith Muslims, one that was tied to a political effort to build a collectiveEuropean identity.Rather surprisingly, the term fantasy is never defined thoroughly, althoughthe author’s central claim is that the Crusades functioned as a way to develop a unified cultural identity for Europe, a project that was itself tied toa fantasy. This project of building a singular Frankish identity, and whatwould eventually come to be a European identity, is the focus of the second,third, and fourth chapters. In them, Falk pays particular attention to the evolutionof the term Saracen, which the Europeans invoked to refer to all ofthe different kinds of Muslims they encountered during the various crusades.The term was initially deployed to specify all Muslims, but by the Third Crusadeit began to connote Eastern European and Baltic Christians as well.Saracens would later be applied to Estonians, Latvians, and Lithuanians duringthe Baltic crusades, which lasted for four centuries. This word eventuallycame to designate anyone who was not European and Christian, and evenChristians like the Basques who had fought the Franks (p. 132).The etymology of this term, which means “empty of Sarah,” emphasizeshow Hagar is recognized as Ishmael’s mother in the Islamic tradition in distinctionto Christianity. The primary motivation for deploying Saracen wasmeant to resolve this outer collective state project of a unified Europe, as wellas to resolve a far more abstract psychological identity conflict that was feltacross Crusader culture. As Falk states: ...